THE ROLE OF BLOCKCHAIN IN INITIATING DIGITAL ACCOUNTING TRANSFORMATION - Loso Judijanto; Dian Ofasari; Selvita Meilansari (Adisam Publisher, 2025)
Blockchain has an important role in initiating digital accounting transformation. In the digital era, technology has changed many aspects of life, including the world of financial accounting. The role of blockchain in the transformation of financial accounting is very significant. By adopting the latest trends such as cloud accounting, artificial intelligence, and blockchain, companies can gain a competitive advantage. The impact includes increased accuracy, operational efficiency and data security. The use of blockchain in accounting applications is very promising, from simplifying regulatory compliance to improving commonly used double entry bookkeeping. The benefits of blockchain in accounting also include its ability to transparently track the use of supply chain funds, eliminate costs resulting from transactions between bank accounts, and increase security and transparency in accounting information systems. Thus, blockchain provides an opportunity to increase security, transparency and efficiency in accounting information systems, as well as reshape traditional accounting practices in the growing discourse on technology- based transformation in accounting. So, overall, blockchain has a significant role in initiating digital accounting transformation by contributing to increasing security, transparency and efficiency in accounting information systems.